2023
DOI: 10.1039/d3se00782k
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of a flexible and shape-adaptive Cd0.5Zn0.5S-based photocatalytic system and its photocatalytic activity for hydrogen evolution from water

Abstract: The development of efficient photocatalysts which can be applied under any conditions and reused easily is important from a practical point of view. For this purpose, a flexible and shape-adaptive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Numerous Cd x Zn 1– x S-based photocatalysts with excellent performance have been developed. Notably, our recent discovery revealed that SrWO 4 serves as an efficient cocatalyst for Cd x Zn 1– x S. The resulting Cd 0.5 Zn 0.5 S/SrWO 4 composite nanoparticles demonstrated remarkable photocatalytic activity for H 2 evolution under visible irradiation . Moreover, we successfully fabricated a flexible and shape-adaptive photocatalytic system with high activity by loading the Cd 0.5 Zn 0.5 S/SrWO 4 nanoparticles on filter papers . This efficient system can be conveniently applied on nonplanar reaction beds and is easily recyclable, showcasing significant application potential in the field of photocatalytic H 2 generation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Numerous Cd x Zn 1– x S-based photocatalysts with excellent performance have been developed. Notably, our recent discovery revealed that SrWO 4 serves as an efficient cocatalyst for Cd x Zn 1– x S. The resulting Cd 0.5 Zn 0.5 S/SrWO 4 composite nanoparticles demonstrated remarkable photocatalytic activity for H 2 evolution under visible irradiation . Moreover, we successfully fabricated a flexible and shape-adaptive photocatalytic system with high activity by loading the Cd 0.5 Zn 0.5 S/SrWO 4 nanoparticles on filter papers . This efficient system can be conveniently applied on nonplanar reaction beds and is easily recyclable, showcasing significant application potential in the field of photocatalytic H 2 generation.…”
Section: Introductionmentioning
confidence: 95%
“…24 Moreover, we successfully fabricated a flexible and shape-adaptive photocatalytic system with high activity by loading the Cd 0.5 Zn 0.5 S/SrWO 4 nanoparticles on filter papers. 25 This efficient system can be conveniently applied on nonplanar reaction beds and is easily recyclable, showcasing significant application potential in the field of photocatalytic H 2 generation. However, the preparation of the aforementioned photocatalytic system is relatively intricate, posing challenges in ensuring stable product quality and hindering large-scale production.…”
Section: Introductionmentioning
confidence: 99%